UVC emitting phosphors obtained by spray pyrolysis - Caiut, J. M. A.; Lechevallier, S.; Dexpert-Ghys, J.; Caillier, B.; Guillot, Ph (Elsevier B.V., 2011)
The broadband inter-configurational (4f(1)5d(1)-->4f(2)) emission of Pr(3+) doped in lanthanum orthophosphate (LaPO(4)) and in calcium pyrophosphate (Ca(2)P(2)O(7)) has been investigated under plasma excitation. The synthesis by spray pyrolysis at moderate temperature followed by a controlled annealing proves to be a very efficient way to produce good quality UVC emitting phosphor Ca(1.92)Pr(0.04)Na(0.04)P(2)O(7) (alpha phase). The emission of this phosphor in the wavelength range 200-350 nm has been measured with a prototype device, which can be employed for anti-microbial testing. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Trivalent praseodymium; Lanthanum orthophosphate; Calcium pyrophosphate; Spray pyrolysis; UVC Emission